St. Hedwig of Silesia: The Ducal Ideal of a Wife in Light of 15th-century “Sermones de sancta Hedwigis” - Kaczor, Ewelina (Respectus Philologicus, 2022)
A collection of 15th-century Latin sermons for the day of St. Hedwig of Silesia (“Sermones de s. Hedwigis”) constitutes the source material for an analysis of matrimonial role models and the ideal of a wife (uxor) in medieval culture. The collection includes 84 sermons about St. Hedwig, preserved in 45 codes of Silesian provenance. The corpus of sermons on St. Hedwig is supplemented by 61 edited versions of “Vita sanctae Hedvigis” written in 47 manuscripts. The present article includes an analysis of St. Hedwig as a married woman, the ideal of a pious wife avoiding the pleasures of the flesh and observing moral norms in marriage, above all in sexual relations.